Within- and between-day test–retest reliability of responses to rapid bilateral anterolateral magnetic phrenic nerve stimulation in healthy humans (ReStim) - Boyle, Kyle G. P. J. M.; Beglinger, Andrea A.; Häusler, Heinrich; Stahel, Anna; Schwarz, Esther I.; Spengler, Christina M. (Frontiers in Physiology, 2025)
BackgroundMechanical ventilation can lead to lung injury and diaphragmatic dysfunction. Rapid bilateral anterolateral magnetic phrenic nerve stimulation (rBAMPS) may attenuate both of the aforementioned issues by inducing diaphragm activation. However, in order for rBAMPS to become part of standard of care, the reliability of inspiratory responses to rBAMPS needs to be established.MethodsEighteen healthy participants (9F) underwent five blocks of 1-s rBAMPS at 25 Hz starting at 20% of maximal stimulator output with 10% increments. Three blocks were completed on the same day to test within-day reliability, and two additional blocks were each completed on subsequent days to test between-day reliability. Mean transdiaphragmatic pressure (Pdi,mean), tidal volume (VT), discomfort, pain, and paresthesia were recorded for each rBAMPS. Relative and absolute reliability of both Pdi,mean and VT were quantified by calculating intraclass correlation coefficients (ICC) and standard error of measurements (SEM), respectively. An ordinal regression was used to determine changes of sensory ratings within and between days.ResultsAt all stimulator outputs, within-day Pdi,mean displayed “good” reliability (ICC range 0.78–0.89). Between days, Pdi,mean reliability was also “good” (ICC range 0.79–0.87) at stimulator outputs of 20%–50% of maximum, but “moderate” (ICC range 0.56–0.72) at stimulator outputs of 60%–100%. SEM for Pdi,mean within day ranged from 0.9 to 3.4 across tested stimulator outputs and increased on average by 1.4 ± 0.9 between days. The VT reliability was “good” to “excellent” within (ICC range 0.82–0.94) and between (ICC range 0.81–0.96) days at all stimulator outputs. SEM for VT within day ranged from 0.08 to 0.36 and from 0.11 to 0.30 between days and tended to be larger at stimulator outputs greater than 50% of maximum. Subsequent blocks within day were associated with decreased discomfort and pain (P ≤ 0.043), while subsequent days were associated with decreased discomfort and paresthesia (P < 0.001).DiscussionrBAMPS appears to induce reliable diaphragmatic contractions, while select sensory responses become blunted over repeated stimulations. However, as reliability is slightly lower between days compared to within day, stimulation parameters may need to be adjusted to achieve similar responses on different days.